Պատմութիւն Բարաղամու եւ Յովասափու - Փայլակ Անթապեան (Տպարան Սրբոյ Յակոբեանց)
Հայերէն Թարգմանութեան նորայայտ մի հնագոյն ընդօրինակութեան առթիւ։
Keywords: Language and Literature; Bibliography; Literature; Translation and interpretation; Christianity